1997
DOI: 10.1136/gut.41.5.619
|View full text |Cite
|
Sign up to set email alerts
|

Antigastric autoantibodies in Helicobacter pyloriinfection: implications of histological and clinical parameters of gastritis

Abstract: Background-It has recently been shown that humoral antigastric autoreactivities occur in a substantial number of Helicobacter pylori infected patients. Aims-To analyse the relevance of such antigastric autoantibodies for histological and serological parameters of the infection as well as for the clinical course. Methods-Gastric biopsy samples and sera from 126 patients with upper abdominal complaints were investigated for evidence of H pylori infection using histology and serology. Autoantibodies against epito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 29 publications
9
74
1
1
Order By: Relevance
“…However, conflicting results have also been reported (24,29). Simultaneous occurrence of H. pylori infection and autoimmune reaction observed in previous investigations (5)(6)(7)(8) or our study population cannot be interpreted to support a causal relationship between bacterial infection and autoimmune response. Because of the crosssectional study design with simultaneous ascertainment of infection, autoimmune response and CAG, temporal relationships between occurrence of bacterial infection, autoimmune response and development of CAG as well as potential disease-related loss of H. pylori infection could not be observed.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…However, conflicting results have also been reported (24,29). Simultaneous occurrence of H. pylori infection and autoimmune reaction observed in previous investigations (5)(6)(7)(8) or our study population cannot be interpreted to support a causal relationship between bacterial infection and autoimmune response. Because of the crosssectional study design with simultaneous ascertainment of infection, autoimmune response and CAG, temporal relationships between occurrence of bacterial infection, autoimmune response and development of CAG as well as potential disease-related loss of H. pylori infection could not be observed.…”
Section: Discussioncontrasting
confidence: 49%
“…Following the discovery of Helicobacter pylori (H. pylori) and the establishment of a causal relationship between H. pylori infection and CAG (1,2), several studies have reported that a considerable number of patients with H. pylori infection also expressed autoantibodies against Hþ/Kþ-ATPase (5)(6)(7)(8). The presence of these autoantibodies in H. pylori infection was also significantly associated with higher fasting serum gastrin levels, a lower pepsinogen I to II ratio, and reduced secretion of gastric acid (8)(9)(10). In addition, pernicious anemia, which was earlier considered as an exclusive complication of autoimmune gastritis (11), was also shown to be accompanied by H. pylori infection (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Microtiter plates (Nunc) were coated with antigen in coating buffer (0.2 M Na 2 CO 3-NaHCO 3 [pH 9.6]) at a concentration of 1 g per well by an overnight incubation at 4°C. After three washes with PBS, 10 11 phages (or 100 l of bacterial supernatant) per well were added and incubated for 2 h at RT. Binding of the phage particles to antigen was detected with the anti-M13 antibody B62-FE2 (Progen, Heidelberg, Germany), a mouse monoclonal antibody specific for the major coat protein pVIII, 10% (vol/vol) in M-PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, about 30% of H. pylori-infected patients develop autoantibodies that are reactive with human gastric antigens, such as the H ϩ ,K ϩ -ATPase. This H. pyloriassociated antigastric autoimmunity has been shown to correlate with atrophy of gastric mucosa (6,10,24). Therefore, further analysis of the humoral immune response following H. pylori infection might give new insight into the pathogenesis of H. pylori gastritis.…”
mentioning
confidence: 99%
“…In addition to the cellular changes induced by the H. pylori proteins, it has become clear in recent years that the bacterial infection and the development of gastritis and stomach cancer are accompanied by autoimmunity Faller et al, 1997), which may also lead to degenerative processes of the stomach mucosa (Negrini et al, 1991).…”
Section: Hensel Et Almentioning
confidence: 99%